(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2024)
The article describes the change in attitude to the idea of the rule of law by the largest Soviet and Russian legal scientist Sergei Sergeevich Alekseev: from the denial of the bourgeois theory of the rule of law in the 70s of the XX century – through the recognition of the ‘finest hour’ of law in the process of forming a socialist rule of law in the 80s of the XX century – to the shift in the focus of the scientist’s attention on the idea of humanistic law. The author also discusses the concept of the rule of law in relation to post-Soviet and modern Russia.